Benchmarking Method to Increase Application of Organic Rice Cultivation Technology - Anjar Hargiyanto; Siti Nurlaela; Gunawan Yulianto (Tropical Plantation Journal, 2023)
Organic farming is the key to agricultural sustainability in the future, but farmers have not implemented it much.  This study aims to determine the application of technology in organic rice cultivation to farmers in the Sri Jati Kalurahan Jatisarono Farmer Group, Kapanewon Nanggulan.  This research uses descriptive qualitative with observation and interviews.  The research was conducted from January to June 2022.  The location determination technique is carried out by purposive sampling.  The data was analyzed by benchmarking, namely comparing businesses at the research site with more advanced organic rice businesses.   The results of the study showed that the application of technology in the Sri Jati Farmer Group compared to the Makmur Farmer Group showed differences in the selection of seed varieties. Pros: on the method of cultivation, and harvesting. While the similarities are in aspects: land processing, seeding seedlings, and weed control. Weaknesses in aspects: fertilization and control of pests. Empowerment activities are emphasized on making fertilizer with rabbit urine and controlling pests with natural ingredients.